Immunogenicity of a Recombinant Influenza Virus Bearing Both the CD4+ and CD8+ T Cell Epitopes of Ovalbumin. (5th October 2011) - Garulli, Bruno; Di Mario, Giuseppina; Sciaraffia, Ester; Kawaoka, Yoshihiro; Castrucci, Maria R.
Abstract : Recombinant influenza viruses that bear the single immunodominant CD8+ T cell epitope OVA 257 − 264 or the CD4+ T cell epitope OVA 323 − 339 of the model antigen ovalbumin (OVA) have been useful tools in immunology. Here, we generated a recombinant influenza virus, WSN-OVA I/II, that bears both OVA-specific CD8+ and CD4+ epitopes on its hemagglutinin molecule. Live and heat-inactivated WSN-OVA I/II viruses were efficiently presented by dendritic cells in vitro to OT-I TCR transgenic CD8+ T cells and OT-II TCR transgenic CD4+ T cells. In vivo, WSN-OVA I/II virus was attenuated in virulence, highly immunogenic, and protected mice from B16-OVA tumor challenge in a prophylactic model of vaccination. Thus, WSN-OVA I/II virus represents an additional tool, along with OVA TCR transgenic mice, for further studies on T cell responses and may be of value in vaccine design.